EFFICACY OF CHLOROQUINE MONOTHERAPY AGAINST PLASMODIUM VIVAX MALARIA: Chloroquine Monotherapy in Malaria - Rasheed, Dr Abdul; Ahmed, Shahid; Saeed, Shahzad (Pakistan Armed Forces Medical Journal, 2010)
Objective: To determine the in vivo efficacy of chloroquine monotherapy against Plasmodium (P.) vivax and frequency of relapse/reinfection. Study Design: Quasi-experimental study. Place and duration of study: Department of Medicine, Combined Military Hospital, Quetta Balochistan, from July 2006 to February 2007. Patients and Methods: One hundred and ninety one subjects with positive plasmodium vivax slide were included in the study. Mean, median, minimum and maximum values along with standard deviation of age and parasite clearance time were calculated. Frequency of relapse/reinfection was estimated and significance was determined by applying test of significance. Results: Of the 191, 21 developed P.vivax relapse/reinfection in the six months follow up. Mean duration of relapse/reinfection was 37.76 days while mean parasite clearance time was almost 30 hours in both initial infection and relapse. Conclusion: Chloroquine monotherapy is still effective in the management of P.vivax malaria in our set up and antirelapse therapy is not routinely indicated.